The Innovation Potential of Established SMEs - Kilsgård, Mona; Örnbratt, Alexander (My University, 2022)
There is a shortage of literature focusing on evaluating the innovation capabilities of long-established, small and medium-sized enterprises (SMEs) in niche technological industries. The purpose of this thesis was to provide an in-depth, comprehensive perspective on the organizational issues affecting innovation capability at this type of firm, and feasible improvements to these issues. To investigate this, fifteen employees across three small subsidiaries in a niche-technology corporate group were interviewed for their perspectives on their company’s characteristics and processes. The findings suggest that such companies experience issues affecting their level of innovation capability on multiple dimensions: resources, processes, culture, and direction. These companies must implement structured systems for process and idea management, and increase collaboration with external actors. They must ensure clear communication across departments and encourage cultures of openness and participation. Managers must encourage learning and implement transparent, fair reward systems for hard work and novel ideas. Lastly, these companies’ strategy is often short-term, and they must develop a long-term mindset and mission statement to combat this. A model summarizing the resource and capability-based understanding of how long-established, niche-technology SMEs can work to improve their innovation capacity was created, and should contribute to a more thorough managerial comprehension of organizational factors essential for this type of firm.
Keywords: corporate culture; idea management system; innovation capability; internal communication; mission statement; niche technology; processes; resources; SME; strategy